Managerial Expertise, Corporate Decisions, and Firm Value: Evidence from Corporate Refocusing - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2014)
This paper investigates how managerial expertise—specifically, industry expertise—affects firm value through divestiture. Using CEOs’ managerial experiences in industries throughout their careers as a measure of their industry expertise, I find that CEOs in diversified conglomerates are more likely to divest divisions in industries in which they have less experience. This finding is consistent with CEOs who divest such divisions in order to refocus on those divisions in which they have specialized—that is, to achieve a better match between their expertise and their firms’ retained assets. Firms that divest for a better CEO-firm match experience significant improvements in operating performance, as well as significant abnormal stock returns that persist for an average of three years following a divestiture. Further, among firms that divest for a better match, those firms with more experienced CEOs realize greater gains in firm value. In contrast, divestitures that increase corporate focus, but do not improve the expertise-asset match, do not lead to long-run increases in firm value.